DIDACTIC PECULIARITIES OF FORMING PROFESSIONAL COMPETENCE OF FUTURE ENGLISH TEACHERS - Riskulova, Kamola (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
It is started in the article some didactic thoughts concerning to conduct a monitoring, to evaluate the level of competence, innovative form, method, means of teaching, competency indicators and typology of competence in forming professional competence of the future English teacher.